Analisis Kemampuan Kognitif Peserta Didik SMA pada Materi Bioteknologi Berbantuan Petunjuk Praktikum Berbasis Guided Inquiry - Ari Ashari; Sahratullah Sahratullah; Bulkiah Bulkiah (Bioscientist : Jurnal Ilmiah Biologi, 2021)
This study aims to determine the initial cognitive abilities of students before being given the results of developing guided inquiry-based biotechnology practicum instructions for high school students. This study uses a quantitative descriptive approach. The research instrument used was a pretest question sheet. The sample of this research is 19 students of SMA Negeri 2 Taliwang. The research data obtained were then analyzed and adjusted to the minimum completeness criteria determined by the school. The results of the study showed that the students' pretest data were as follows: the standard KKM score for SMA Negeri 2 Taliwang was 75, the average score obtained by students was 12.21 with an average score of 61.05 predicate D, and the KKM category was incomplete. The initial cognitive abilities of students are still lacking. The value of the cognitive domain is as follows: level C4 (analyzing) with a total of 12 questions obtained a percentage of 60.1%, C5 (evaluating) with a number of questions as many as 1 obtained a percentage of 57.9%, and C6 (proving) with a number of questions as many as 7 obtained a percentage of 63.2%.